Pengaruh Ukuran Perusahaan, Leverage, Kinerja Keuangan Terhadap Nilai Perusahaan Manufaktur Di Bursa Efek Indonesia - Ngurah Cahya Adi Kusuma; IGN Putra Suryanata (Jurnal Manajemen dan Bisnis, 2016)
The aim of this study is 1) To know and analyze the effect of firm size on financialperformance 2) To determine and analyze the effect of leverage on the company's financialperformance 3) To know and analyze the effect of firm size on corporate value 4) To knowand analyze the effect of leverage the value of the company 5) To know and analyze the effecton the value of the company's financial performance. The location study performed oncompanies listed in the Indonesia Stock Exchange. Data collection technique useddocumentation study were obtained from www.idx.co.id. The number of samples taken was 27manufacturing company. Data were analyzed with path analysis with AMOS program version20. The results showed that 1) The size of the company and significant positive effect onfinancial performance, 2) Leverage a significant negative effect on the company's financialperformance, 3) The size of the company and significant positive effect the value of thecompany, 4) Leverage significant negative effect on the value perusahaan5) financialperformance and significant positive effect on firm value.Keywords: firm size, leverage, financial performance, the company's value